Iron status, anemia and functional capacity in adults with congenital heart disease: a single center analysis. (25th November 2020) - Karathanos, A; Simon, I; Brockmeyer, M; Lin, Y; Parco, C; Krieger, T; Schulze, V; Hellhammer, K; Kelm, M; Zeus, T; Wolff, G
Abstract: Background: Iron is essential to the mitochondrial energy production in cardiomyocytes and its depletion is negatively associated with symptoms, functional capacity, quality of life and outcomes in patients with heart failure – independent of anemia. The relevance of iron deficiency in adults with congenital heart disease however has not been evaluated to date, and we thus aimed to evaluate it in an all-comer cohort of patients with congenital heart disease in correlation with symptoms and functional capacity. Methods and results: 527 patient cases from one referral center over 2 years were evaluated concerning their iron status, anemia, functional capacity and ejection fraction of their systemic ventricle. 264 were female, 94 had a shunt lesion, 96 had left-sided obstructive lesions, 181 right-sided lesions, while 108 were considered to have complex lesions and 28 were cyanotic. The median age was 34 years, the mean BMI was 25.2±5 kg/m 2, 429 patients had a normal ejection fraction and 34 moderately and severely depressed. 35 patients were classified as NYHA III, and 56 as NYHA II, while their functional capacity was evaluated via cardiopulmonary testing with a mean VO2max/kg of 22.6±6.5 and mean 69±17% of the expected. The mean serum iron concentration was 99.4±42.3 mcg/dL, their mean transferrin saturation was 27.36±13%, the mean ferritin concentration was 130.8±185 ng/mL, the mean soluble transfer factor was 1.3±0.66 mg/l and their mean Hemoglobin 14.8±2 mg/dL, while the mean MCV was 88±5.3 and the mean MCHC 33.7±1.4. 40 patients were anemic according to the WHO definition for anemia, in 28 of those patients that was already known. Iron deficiency according to stratified according to ferritin was present in 53 patients. However, when stratified according to the heart failure guidelines definition for iron deficiency 299 patients were found affected. Using the soluble transferrin receptor (sTfR) and sTfR-ferritin index iron deficiency was suspected in 10 additional individuals. Iron deficiency was associated with the ejection fraction (p=0.0001) - patients with moderately or severely depressed systemic ventricular function more often were diagnosed with iron deficiency (p=0.007)-, while it did not correlate with functional NYHA classification (p=0.622) or functional capacity (p=0.1 and 0.057). Iron deficiency was also not found significantly different amongst congenital defects but did correlate with all laboratory iron studies. Conclusions: In this ambulatory population of adults with congenital heart disease we found an association of ejection fraction with iron deficiency, however no association of iron deficiency with functional capacity. The question arising is if a new definition of iron deficiency anemia in congenital heart disease similar to heart failure would be of clinical value. Funding Acknowledgement: Type of funding source: None